Wind farms and griffon vultures: evidence that under certain conditions history is not-always turbulent - Farfán-Aguilar, Miguel Ángel; Díaz-Ruiz, Francisco; Duarte, Jesús; Martín-Taboada, Adrián; Roman-Muñoz, Antonio (Elsevier, 2023)
Since the early stages of wind energy development, there has been concern about the potential impact of wind farms on wildlife, particularly birds and bats. However, the lack of long-term studies has hindered the assessment of the real effect of wind farms on mortality and distur- bances. We show a case study in which we researched during the nestling rearing period the long- term effects of a wind farm located in southern Spain on the abundance, displacement, and mortality of the Griffon Vulture, a raptor considered very sensitive to collisions. After 13 years of operation, observation and abundance rates increased significantly during the study period. Griffon Vultures avoided flights between wind turbines by flying at the ends of the rows or through the existing corridor between alignments of wind turbines. Our results are in line with the theory that birds may become habituated to the presence of wind farms suggesting that, under certain conditions, it could be possible to reconcile the presence of wind farms with raptor conservation. Environmental agencies should not only require robust pre-construction surveys, but also that wind energy developers monitor bird abundance and behaviours throughout the lifetime of a wind farm. Since not all wind farms are associated with high mortality rates, such an initiative could be key to gaining more knowledge on the association between wind-farm loca- tion, design and risk to birds.
Keywords: Biología; Aves - Poblaciones; Buitres leonados; Impacto ambiental - Análisis; Energía eólica; Bird abundance; Conservation; Environmental impact; Gyps fulvu; Renewable energy